Produção audiovisual e leitura paleográfica a partir de documentos do acervo da Cúria Metropolitana de Belém: uma experiência extensionista em Arquivologia - OLIVEIRA, Maisa Monteiro de (2023)
This study deals with the diffusion of documentary collections and extensionist experiences acquired in the context of the Extension Project Diffusing Archives Unfolding Memoirs and Narrating Stories (2021-2022), whose main purpose is the diffusion/dissemination of the archives of Pará institutions, this is, Land Institute from Pará; Superintendence for the Development from Amazon; Metropolitan Curia of the Archdiocese of Belém from Pará; Public Archive from State of the Pará and Municipal Elementary and Middle School Dr. Freitas. Using as theoretical support the concepts of Archival Diffusion; University Extension; Documentary Heritage and Memory. The narrative of this written work is inserted in a pandemic scenario and on some adversities faced during this period, for this reason the diffusionist activities were carried out from the production of visual and audiovisual materials for later publication on the various social media, thus promoting social distancing at a very delicate time in humanity history. The objective of this research is to present the results obtained with the mentioned extension project. The indicated research also seeks to highlight a specific audiovisual product and the unfolding of its construction, showing in practice the multi, trans and interdisciplinary relationships of Archival Science with other disciplines and areas of knowledge.